Design of a Portable Water Purification Flask Using a Mini Diaphragm Pump System - CHONG KAR YEW, JONATHAN; Assoc. Prof. Ir. Dr. Sia Chee Kiong, (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Access to safe drinking water remains a global challenge, particularly for outdoor enthusiasts and individuals in remote areas. This study aims to design a compact, lightweight, and user-friendly portable water purification flask that integrates a manual diaphragm pump, dual-stage filtration, and UV-C disinfection. The project adopted a structured engineering design methodology, incorporating ergonomic analysis and material selection, and utilized SolidWorks for conceptual and embodiment design. The final product measures 267.3 mm in height, with a 75 mm base diameter and an empty weight of 455 g, making it suitable for outdoor use. Performance analysis revealed that the mini manual diaphragm pump operates at 25 strokes per minute, delivering 10 mL per stroke, resulting in a nominal flow rate of 250 mL/min. After accounting for filtration resistance, the effective flow rate is 175 mL/min, enabling the purification of 500 mL of water in approximately 3 minutes. Drop test results indicated a maximum von Mises stress of 10.5 MPa and a maximum displacement of 25.4 mm, both within safe limits for HDPE material. These findings confirm the design’s practicality, durability, and efficiency, providing a promising solution for reliable water purification during outdoor activities.